Clinicopathological analysis of salivary gland tissue from patients with IgG4-related disease. (2nd July 2016) - Takano, Kenichi; Nomura, Kazuaki; Abe, Ayumi; Kamekura, Ryuta; Yamamoto, Motohisa; Ichimiya, Shingo; Takahashi, Hiroki; Himi, Tetsuo
Abstract: Conclusion The diagnosis of immunoglobulin G4-related disease (IgG4-RD) should be based on the morphology of tissue biopsy, and this study recommends a submandibular gland (SMG) biopsy for accurate diagnosis and to exclude malignant disease.Objective To clarify which type of biopsy specimen (SMG or labial salivary gland [LSG]) should be taken from patients with IgG4-RD.Methods This study included 33 patients with IgG4-RD (21 women; 12 men) who were subjected to both SMG and LSG biopsies at Sapporo Medical University between 2011–2015. Tissues obtained from the SMG and LSG specimens were evaluated.Results All SMG specimens satisfied the diagnostic criteria for IgG4-RD, whereas 19 (57.6%) LSG specimens satisfied the diagnostic criteria for IgG4-RD. Histological evaluation showed fibrosis in all the SMG specimens and in eight LSG specimens (24.2%). Obliterative phlebitis was seen in nine SMG specimens (27.3%), but it was absent in all the LSG specimens.